Improving crystallinity and ordering of PBTTT by inhibiting nematic to smectic phase transition via rapid cooling. (21st September 2022) - Zhang, Lu; Li, Hongxiang; Zhao, Kefeng; Zhang, Tao; Liu, Duo; Wang, Sichun; Wu, Fan; Zhang, Qiang; Han, Yanchun
Abstract: The liquid crystalline (LC) phase can promote the long-range ordering of conjugated polymer films. Therefore, the effects of different single LC phases and the coexistence of multiple LC phases on film morphology deserve further study. In this work, we found that distinct film morphologies can be obtained by undergoing different LC transition processes. It was demonstrated that Poly(2, 5-bis(3-alkylthiophen-2-yl)thieno[3, 2-b]thiophene) (PBTTT) undergoes a high-temperature nematic LC I phase and a low-temperature smectic LC Ⅱ phase by optical images, in-situ UV–vis spectroscopy and Fourier transform infrared spectroscopy (FTIR). When the PBTTT is rapidly cooled from the melt to solid thin film at 130 °C/min, the films crystallize from LC I directly and keep the nematic-like texture. When the melt is slowly cooled at 1 °C/min, the films crystallize after transforming from LC I to LC II and retain the smectic-like texture. The former films exhibit 24.5 times higher crystallinity than the latter. Meantime, the lamellar packing d100 distance increases from 21.06 Å to 23.85 Å, and the intercrystallite distance increases from 9 nm to 25 nm, respectively. The restraint chain mobility in the highly ordered smectic phase and the nanoconfinement effect induced by phase separation between LC I and LC II are responsible for the reduced crystalline order in the films experienced by LC I and LC II. This work emphasizes the importance of LC phases and rational annealing programs on morphology design. Graphical abstract: The morphology differences between films have different crystallization initial states, the nematic phase and the smectic phase. Image 1 Highlights: Investigated the liquid crystal phase transition of PBTTT. Reported the cooling rate-controlled crystallization routes. Obtained a distinct high crystallinity morphology at fast cooling.